Evaluation of Medical Waste Management in Three Hospitals in Basrah Governorate,Iraq - Jawad Khaled , Sarah; Abdul-Ameer Ali, Wissam (University of Thi-Qar Journal of Science, 2023)
Health institutions create between 10 and 15 percent of their total waste as hazardous waste, consisting of substances contaminated with patient blood or bodily secretions, and need special handling to make it safe for disposal due to its environmental and public health risks. The data was collected by designing a self-assessment questionnaire. Three government hospitals in Basrah were randomly selected.The results showed that only one hospital got a high level, while the remaining two hospitals received a medium level because of transportation issues and inadequate medical waste storage. As it related to assessing healthcare providers' knowledge, attitudes, and practices toward medical waste, the results were positive at 91.6 % knowledge level, 85.4 % attitude level, and 87.8 % practice level. The situation of medical waste in the governorate requires additional effort on the part of the responsible authorities in terms of adopting new technologies in hospital waste management and promoting more education and training for staff.